A Survey on Visible Light Communication (International Journal of Engineering and Computer Science, 2014)
This paper introduces the concept of visible light communication (VLC). Visible-light communications (VLC) is a technology for wireless communication using light that can be perceived by the naked eye. VLC uses frequencies other than radio, and they are unrestricted and licence free. The urgent need of VLC is to overcome the problems faced in RF communication. Unlike existing methods of wireless communication, the visible light portion of the electromagnetic frequency spectrum is used in VLC to transmit information. Visible light communication (VLC) refers to the communication technology which utilizes the visible light source as a signal transmitter, the air as a transmission medium, and the appropriate photodiode as a signal receiving component. This paper provides an overview of applications and design challenges for VLC, compare it with other existing communication technologies and presents the modulation techniques used